Taxonomic and Phylogenetic study of Termitomyces entolomoides in western Assam - Rava, M.; Ali, R.; Das, S. (International Journal of Scientific Research in Biological Sciences, 2019)
Termitomyces genus is paleotropical in nature and is known for its obligate symbiotic association with termites belonging to Macrotermitinae. The Termitomyces sample was collected during the monsoon and post monsoon period (April-October). The basidiocarp was oven dried and used for the macro-morphological and micro-morphological studies. Identification of fungi using morphological characters is very complicated and error prone. Furthermore, internal transcribed spacer (ITS) region 1, 5.8S rRNA gene and ITS 2 region was amplified using ITS 1 and ITS 4 primer pairs. The amplicon of ~600 bps was sequenced and subjected to Phylogenetic analysis in MEGA X sowftware package. Newly obtained sequence and 19 sequences of Termitomyces from NCBI GenBank were aligned using MAFFT. Phylogenetic tree was constructed using Maximum Likelihood method with bootstrap values of ≤ 70 %. The morphological characters and molecular data indicate the studied sample as Termitomyces entolomoides. Phylogenetic relationship of the studied species with 19 Asian Termitomyces species obtained from NCBI GenBank is established and is clearly monophyletic.